A Clinico-Epidemiological Study on Porokeratosis - Trishala Shirahatti; H Bangaru; S Sathish (Wolters Kluwer Medknow Publications, 2024)
Porokeratosis (PK) is a chronic progressive disorder of keratinization characterized clinically by hyperkeratotic papules or plaques surrounded by a threadlike, elevated border that expands centrifugally. Pathogenesis involves heterozygous mutations in mevalonate kinase enzyme. The most common variants are disseminated superficial actinic porokeratosis (DSAP) and PK of Mibelli. All forms show a thin column of parakeratosis, the cornoid lamella, representing the active border. Dermoscopy reveals central brownish discoloration surrounded by a single hypopigmented band and a peripheral 'white track'. Long-standing cases of PK may undergo malignant transformation. UV-protection and topical agents, such as 5-fluorouracil, imiquimod, calcipotriol, tretinoin and oral retinoids are helpful. To study the clinical and epidemiological pattern of PK and the clinico-dermoscopic and histopathological correlation of PK. A prospective cross-sectional study was conducted on the patients attending the dermatology outpatient department (OPD) over 9 months with suspected features of PK. These patients were evaluated clinically and subjected to dermoscopy and histopathology. Statistical Package for the Social Sciences (SPSS) Of 11 patients, there were four (36.36%) males and seven (63.66%) females. The youngest was 18-year-old boy, and the eldest was 63-year-old man. The clinically most common type was PK of Mibelli with five (45.45%) cases. The most common dermoscopic feature observed was double-marginated, white peripheral border. The most common histopathological feature noted was cornoid lamella. PK is a rare skin disorder with a wide spectrum of clinical variants. Dermoscopy and histopathology aid in diagnosis, whereas dermoscopy plays a pivotal role in early and non-invasive diagnosis. Regular follow-up is mandatory to watch for the development of malignancies in a few variants.